(untitled) (Scientific journal of the Fergana State University, 2025)
This article broadly covers the semantic area of ​​words found in the texts of folklore genres belonging to English and Uzbek culture, and also pays attention to their meaning and application. During the study, the semantic features of words were studied through comparative typological analysis. In addition, descriptive-quantitative, structural-semantic, mathematical-statistical analysis methods were used, the meaning of words and their role in the text were deeply analyzed. The article also uses a conceptual approach and contextual analysis methods, the meaning of words in context, their cultural-semantic aspects are widely studied.